2019
DOI: 10.1002/smtd.201900356
|View full text |Cite
|
Sign up to set email alerts
|

Greatly Enhanced Electrocatalytic N2 Reduction on TiO2 via V Doping

Abstract: As a sustainable alternative technology to the Haber–Bosch process, electrochemical N2 reduction offers the hope of directly converting N2 to NH3 at ambient conditions. However, its efficiency greatly depends on screening high‐active electrocatalysts for the N2 reduction reaction (NRR). Here, the recent experimental finding that V is an effective dopant to greatly improve the NRR performances of TiO2 toward ambient N2‐to‐NH3 fixation with excellent selectivity is reported. In 0.5 m anhydrous lithium perchlorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(56 citation statements)
references
References 82 publications
0
54
0
Order By: Relevance
“…TiO 2 is highly adaptable as a semiconductor catalyst because of its long‐term thermodynamic stability, natural abundance, and nontoxicity . Recent studies have demonstrated that TiO 2 with oxygen defects has good electrocatalytic activity for the NRR, and heteroatoms (B, C, V, and Zr,) are effective dopants to enhance the NRR performances of TiO 2 catalysts. However, Ti‐based catalysts that simultaneously achieve a large NH 3 yield with a high Faradaic efficiency (FE) are not available thus far.…”
Section: Figurementioning
confidence: 99%
“…TiO 2 is highly adaptable as a semiconductor catalyst because of its long‐term thermodynamic stability, natural abundance, and nontoxicity . Recent studies have demonstrated that TiO 2 with oxygen defects has good electrocatalytic activity for the NRR, and heteroatoms (B, C, V, and Zr,) are effective dopants to enhance the NRR performances of TiO 2 catalysts. However, Ti‐based catalysts that simultaneously achieve a large NH 3 yield with a high Faradaic efficiency (FE) are not available thus far.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, the results were very high when NRR was carried out in 0.5 m LiClO 4 electrolyte. [32] At −0.4 V, V-TiO 2 exhibited efficiency as high as 15.3%. The excellent performance was attributed to increased defects, synergetic effects between Ti and V and change in electronic conductivity of TiO 2 caused by V doping.…”
Section: (5 Of 44)mentioning
confidence: 95%
“…Nonetheless, the expensiveness limits its broad applications. Therefore, much attention has focused on noble‐metal‐free catalysts . Rare‐earth elements have received research attention in the past few years due to their potential applications in catalysis fields, optics, biological labeling, etc.…”
Section: Figurementioning
confidence: 99%